IL‐16 processing in sentinel node regulatory T cells is a factor in bladder cancer immunity. (30th August 2020) - Krantz, David; Mints, Michael; Winerdal, Malin; Riklund, Katrine; Rutishauser, Dorothea; Zubarev, Roman; Zirakhzadeh, Amir Ali; Alamdari, Farhood; Johansson, Markus; Sherif, Amir; Winqvist, Ola
Abstract: In the effort of developing new immunotherapies, the sentinel node (SN) has proven a promising source from which to harness an effective antitumour T cell response. However, tumour immune escape, a process in which regulatory T cells (Tregs) play a central role, remains a major limiting factor. Therefore, there is a clear need to increase the knowledge of Treg function and signalling in sentinel nodes. Here, we set out to explore whether the proteome in SN‐resident T cells is altered by the tumour and to identify key proteins in SN T cell signalling, focusing on Tregs. Five patients with muscle‐invasive urothelial bladder cancer were prospectively included. Mass spectrometry was performed on two patients, with validation and functional studies being performed on three additional patients and four healthy donors. At cystectomy, SN, non‐SN lymph nodes and peripheral blood samples were collected from the patients and T cell subsets isolated through flow cytometry before downstream experiments. Proteomic analysis indicated that growth and immune signalling pathways are upregulated in SN‐resident Tregs. Furthermore, centrality analysis identified the cytokine IL‐16 to be central in the SN‐Treg signalling network. We show that tumour‐released factors, through activating caspase‐3, increase Treg IL‐16 processing into bioactive forms, reinforcing Treg suppressive capacity. In conclusion, we provide evidence that Tregs exposed to secreted factors from bladder tumours show increased immune and growth signalling and altered IL‐16 processing which translates to enhanced Treg suppressive function, indicating altered IL‐16 signalling as a novel tumour immune escape mechanism.